ALIGNING STRATEGIC HR MANAGEMENT WITH BUSINESS OBJECTIVES: EXAMINING THE EFFECT ON ORGANIZATIONAL EFFECTIVENESS AND PERFORMANCE - Arora, Sonam; Malhotra, Latika; Ruhil, Madhu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s dynamic business environment, aligning strategic Human Resource (HR) management with organizational objectives is crucial for enhancing effectiveness and performance. This paper explores the impact of strategic HR management on organizational effectiveness and performance by examining how aligning HR practices with business goals contributes to overall success. It delves into the theoretical foundations of strategic HR management, emphasizing the role of HR in shaping organizational culture, driving performance, and achieving strategic objectives. The study uses a combination of literature review and case studies from various industries to highlight best practices and illustrate how strategic HR alignment leads to competitive advantage. Key findings reveal that organizations that successfully integrate HR strategies with business goals experience improved employee engagement, higher productivity, and better organizational outcomes. The paper concludes with practical recommendations for HR professionals and business leaders on how to effectively align HR strategies with organizational objectives to drive sustainable growth and performance.